The Interference of Arabic Prepositions in Emirati English - Jean Pierre Ribeiro Daquila (Sci, 2021)
The bond between England and the UAE date back to over 220 years ago. This article explored the interference of Arabic prepositions in the English used in the United Arab Emirates (UAE), and their occurrences in light of gender and level of education, two important social variables related to linguistic behavior. To do so, participants translated 20 sentences in Arabic into English as well as filled in 30 gaps in sentences in English with the missing prepositions. We also experimented how musical intelligence improved the Emiratis’ performance regarding prepositions. An experiment was carried out to verify if participants from the experimental group, who received training on prepositions through music, obtained better results compared to the control group, who received training through a more traditional way (by listening to the instructor and repeating).